Assessing social cognition in people with a diagnosis of dementia: Development of a novel screening test, the Brief Assessment of Social Skills (BASS-D). Issue 2 (7th February 2020) - Kelly, Michelle; McDonald, Skye
ABSTRACT: It is well established that people with a diagnosis of dementia can experience impaired social cognition. This study aimed to develop a new screening test for assessing social cognition impairments in dementia and to examine its convergent and construct validity in normal healthy adults and people with dementia. Materials from established tests with proven sensitivity to social cognition impairments were adapted to create a short screening test that uses pictures and simple text. The Brief Assessment of Social Skills-Dementia (BASS-D) is administrable bedside and examines emotion recognition, face identification, empathy, theory of mind, social disinhibition, social reasoning and memory for faces. The BASS-D was administered to 28 healthy older adults ( M age = 76.71, SD = 6.15) and 26 participants with a diagnosis of dementia ( M age = 81.38, SD = 9.39). Participants also completed a number of measures of social cognition and the Addenbrooke's Cognitive Examination III. Each of the BASS-D domains demonstrated adequate convergent validity ( r = .32-.81), with the exception of Face Memory. Significant differences in total BASS-D total scores were observed between the healthy adults and participants with a diagnosis of dementia. BASS-D correlated with some measures of dementia but not others. In conclusion, the BASS-D holds promise as a short screen for assessing social skills in dementia that will assist families and carers in managing social cognition impairments. Further development of normative data in a larger set of healthy older adults along with evidence for test–retest reliability will advance this tool toward clinical utility.